2020
DOI: 10.1109/mcse.2019.2949413
|View full text |Cite
|
Sign up to set email alerts
|

Attributing and Referencing (Research) Software: Best Practices and Outlook From Inria

Abstract: Software is a fundamental pillar of modern scientific research, across all fields and disciplines. However, there is a lack of adequate means to cite and reference software due to the complexity of the problem in terms of authorship, roles and credits. This complexity is further increased when it is considered over the lifetime of a software that can span up to several decades. Building upon the internal experience of Inria, the French research institute for digital sciences, we provide in this paper a contrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Network. It is a funding agency with a Research Software Program 22 that has organized the Canadian Research Software Conference in 2018 23 .…”
Section: Canarie 21 Is Canada's National Research and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Network. It is a funding agency with a Research Software Program 22 that has organized the Canadian Research Software Conference in 2018 23 .…”
Section: Canarie 21 Is Canada's National Research and Educationmentioning
confidence: 99%
“…Version 1 23 September 2019 Reviewer Report https://doi.org/10.5256/f1000research.21946.r52525 © 2019 Merlet J. This is an open access peer review report distributed under the terms of the Creative Commons , which permits unrestricted use, distribution, and reproduction in any medium, provided the original Attribution License work is properly cited.…”
Section: Open Peer Review Current Peer Review Statusmentioning
confidence: 99%
“…Following [9], we distinguish software artifact reference from software project citation, that serve different purposes.…”
Section: A Software Reference Versus Citationmentioning
confidence: 99%
“…The two activities are intertwined, and sometimes citing the project without also referencing artifacts is not satisfactory. But for the specific needs of reproducibility, referencing software artifacts is often sufficient and may be easily done without, e.g., having to track down credit attribution, a vastly more difficult task that is worth a research article on its own [9].…”
Section: A Software Reference Versus Citationmentioning
confidence: 99%
“…We can work to build attribution into the scientific workflow, but human judgement is still required to assess the relative value of various contributions. Indeed, a study of software attribution found that automating credit mechanisms can lead to perverse metrics and incentives that can falsely represent the value of a contribution (Alliez et al 2019).…”
Section: Tracking Use and Impactmentioning
confidence: 99%